Bottoms up: the role of gut microbiota in brain health. (13th January 2019) - Radisavljevic, Nina; Cirstea, Mihai; Brett Finlay, Barton
Summary: The gut microbiota affects many aspects of human health, and research, especially over the past decade, is demonstrating that the brain is no exception. This review summarizes existing human observational studies of the microbiota in brain health and neurological conditions at all ages, as well as animal studies that are advancing the field beyond correlation and into causality. Potential mechanisms by which the brain and the gut microbiota are connected are explored, including inflammation, bacterially‐produced metabolites and neurotransmitters and specific roles for individual microbes. Finally, important challenges and potential mitigation strategies are discussed, as well as ways in which some of these same challenges can be harnessed to advance our understanding of this complex, exciting and rapidly evolving field.